Social inequality - Warwick-Booth, Louise; Malvern, Andrew (Los Angeles ; London ; New Delhi ; Singapore : SAGE, 2022)
"This book provides up to date discussion and evidence about inequalities, social divisions and stratification. Its innovative style engages readers and encourages them to reflect upon the many dimensions of social inequality"--
Includes bibliographical references and index.
ESS
Keywords: Equality; Social Sciences